VD_FINDINFO AP / 2011 / 144 vom 11. Juni 2010 - VD Tribunal cantonal (2010)
ACTION EN PAIEMENT, SUCCESSION, GESTION D'AFFAIRES IMPARFAITE | 640 al. 1 CC, 149 al. 1 CO, 420 al. 1 CO, 420 al. 2 CO, 420 al. 3 CO, 422 al. 1 CO